Psychological characteristics and motivation for change in men convicted of intimate partner violence (2011)
Knowledge about men who are violent with their partners is essential to reduce the risk of the victims, as well as to design treatment programs. This paper examines some of the psychological characteristics of the offenders and their motivation to change. We present a descriptive study of a group of men who participated in a program designed to treat men convicted of domestic violence crime. We analysed data from the following questionnaires: URICA, HADS, SCL-90-R, BDHI, IRI and IPD. The results show that the men in the study sample were mostly in the contemplation stage regarding their willingness to change. Concerning psychological characteristics, the results show low scores in depression, anxiety and hostility, with moderate scores regarding empathy towards the victim and the presence of distorted thinking. Finally, no statistically significant differences were found between the initial predisposition of the subjects to change and the other variables studied